Peduli Lingkungan bagi Anak Berkebutuhan Khusus (ABK) dengan Penerapan Tong Sampah Ceria - Rahmadhani Fitri; Hendra Fahruddin Siregar; Adi Sastra PengalamanTarigan (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2019)
Anak Berkebutuhan Khusus (ABK) are children with distinct special characteristics without always showing mental, emotional or physical disabilities; One of them is Tunagrahita. The SLB C Muzdalifah is aimed at the education of disabled or individuals who do not have the ability to adapt so they need to get learning about self-development and socialization. Education in the SLB facing problems, such as the level of students ' intelligence, limited students ' independence, poor general public view, and environmental utilization as a learning medium. Garbage is the remnant of human day activities and/or solid-form natural processes (UU No. 18 year 2008). Medan Cleanliness Office recorded the volume of garbage as much as 1,535 tons of garbage/day that entered the final disposal (TPA). Trash is scattered to make the presence of neglected garbage. Implementation method with socialization and workshop so gained evaluation. Socialization is one way to give knowledge about waste and environment. Workshop with graffity that is painting garbage cans is an attraction of ABK in developing creativity. Strengthening creativity in art skills is able to explore the potential of students. The ability to describe modestly is contained with selection of objects, images and knowledge symbols is simple. This potential is able to prove that they are able to describe a single/simple topic.